Polyurethane-Keratin Membranes: Structural Changes by Isocyanate and pH, and the Repercussion on Cr(VI) Removal - María D. Manrique-Juárez; Ana L. Martínez-Hernández; Oscar F. Olea-Mejía; Jaime Flores-Estrada; José L. Rivera-Armenta; Carlos Velasco-Santos (International Journal of Polymer Science)
Keratin has the capacity to interact with metal ions. In order to take advantage of this potential, a novel membrane with polyurethane and keratin has been developed and studied for removal of Cr(VI) from aqueous solution. Physicochemical and morphological properties of these hybrid membranes were studied, varying synthesis parameters such as the type of isocyanate and pH in keratin solution. The effects of using diphenyl-methane-diisocyanate or toluene-diisocyanate and modifying the pH in keratin solutions were evaluated by scanning electron microscopy, Fourier transform infrared spectroscopy, and dynamical mechanical analysis. Results show that pH has a strong influence on morphology and on Cr(VI) removal efficiency. When pH in keratin solution is low (2.5), the protein separates from water, and a more closed cell in the membrane is obtained affecting its mechanical properties. The removal efficiency of Cr(VI) was also assessed at different pH values of chromium solutions. These results show that when pH of the Cr solution is acidic (at 1.5), the Cr(VI) removal percentages increase significantly, reaching up to a 58%. Thus this paper demonstrates the successful combination of synthetic and natural polymers depending on the process parameters to be applied in the critical purpose of remediation of Cr(VI) contamination.